NEW HUMAN BODY PARTS DISCOVERED (Iraqi Journal of Medical Sciences, 2016)
Reports about new discoveries in human anatomy could help in the progress of medical care in term of diagnosis and management. Among the many of these was the hidden system of vessels discovered in the human brain in 2015, the anterolateral ligament of the knee joint describe in 2013, Dua's layer discovered in the human cornea in 2013, and the description of the anatomic structure of the G-spot done in 2012. These new part of the human body may be more properly considered as newly discovered variations in the human body.Keywords: Anatomy, human discoveries, brain lymphatics, knee joint, Dua's layer, G-spot.
Keywords: Anatomy; human discoveries; brain lymphatics; knee joint; Duas layer; Gspot